2019
DOI: 10.1590/1807-1929/agriambi.v23n6p393-399
|View full text |Cite
|
Sign up to set email alerts
|

Gas exchanges and growth of cotton cultivars under water salinity

Abstract: Indication of salt-tolerant cotton cultivars can make the agricultural exploitation with saline water irrigation feasible in the Brazilian semi-arid region. Thus, this study aimed to evaluate the gas exchanges and growth of cotton cultivars irrigated with saline water. The study was conducted in pots adapted as drainage lysimeters under greenhouse conditions, using a sandy loam Entisols as substrate. Treatments were distributed in completely randomized design, in 5 x 2 factorial arrangement, relative to five l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
2
3
0
Order By: Relevance
“…A 26.1% reduction in A (9.54 mmol CO 2 m -2 s -1 ) was observed between the highest (6.3 dS m -1 ) and the lowest (0.3 dS m -1 ) salinity levels. These A results corroborate those found by Silva et al (2019b) in a study with cotton cultivars BRS 368 RF and BRS Safira under salt stress (ECw ranging from 1.5 to 7.5 dS m -1 ), where a 5.1% decrease was observed per unit increase in ECw. The authors attributed this result to the decline in stomatal conductance and transpiration, a process that can restrict the transfer of CO 2 to the leaf and contribute to the reduction of A.…”
Section: Resultssupporting
confidence: 91%
“…A 26.1% reduction in A (9.54 mmol CO 2 m -2 s -1 ) was observed between the highest (6.3 dS m -1 ) and the lowest (0.3 dS m -1 ) salinity levels. These A results corroborate those found by Silva et al (2019b) in a study with cotton cultivars BRS 368 RF and BRS Safira under salt stress (ECw ranging from 1.5 to 7.5 dS m -1 ), where a 5.1% decrease was observed per unit increase in ECw. The authors attributed this result to the decline in stomatal conductance and transpiration, a process that can restrict the transfer of CO 2 to the leaf and contribute to the reduction of A.…”
Section: Resultssupporting
confidence: 91%
“…The results of this research revealed that the increase in the electrical conductivity of the irrigation water compromised the instantaneous efficiency of the carboxylation. These results corroborated those reported by SILVA et al (2019), who found that salinity compromises carbon utilization in cotton crop (Gossypium hirsutum l.).…”
Section: Discussionsupporting
confidence: 92%
“…There was a reduction in the number of leaves with the increase in salt concentration, and a decreasing linear model was fitted for all cultivars (Figure 1); for each unit increase in ECw, there were reductions of 7.2, 5.98, 12.65 and 8.33% for the cultivars Branquinha, Manteiguinha, Espírito This result reveals superiority of the cultivar Manteiguinha, that is, evidencing greater tolerance to the decrease in cell elongation rate and low water absorption caused by excess soluble salts (SILVA et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…ns = not significant Table 3 -Summary of the joint analysis of variance (F values) for plant height (PH), leaf area (LA), number of leaves (NL) and stem diameter (SD) of four lima bean cultivars as a function of different levels of salinity Pereira Filho et al (2017a), evaluated the effect of salinity on cowpea crop and also verified a reduction in plant height with the increase in the electrical conductivity of irrigation water. Silva et al (2019), studied cotton crop irrigated with saline water and observed that salt stress inhibited plant height.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation